2020
DOI: 10.18203/2320-1770.ijrcog20201778
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of misoprostol oral versus vaginal route for induction of labour

Abstract: Background: Induction of labour at term is a common obstetric intervention. Prostaglandin E2 has been the agent of choice for pre-induction of cervical ripening for several decades. In recent time, prostaglandin E1 analogue (misoprostol) is a preferred new agent for pre-induction cervical ripening and labour induction owing to inexpensive, stable in room temperature, administrable through several routes. The ideal dose, route, and frequency of administration of misoprostol are still under investigation.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The dosing and timing of misoprostol ranges 25-50 mcg every 2-6h.However,ina study of balancing efficacy and safety, the minimum efficacious dose associated with less complication is 25 mcg [38], while the vaginal compared with the oral route appears to offer significant clinical advantage in successful vaginal delivery [39]. Dinoprostone is prostaglandin E2 that comes in two popular preparations as Cervidil, a control release hydrogel suppository 10 mg vaginal inserted every 12 h at 0.3 mg/h.…”
Section: Prostaglandinsmentioning
confidence: 99%
“…The dosing and timing of misoprostol ranges 25-50 mcg every 2-6h.However,ina study of balancing efficacy and safety, the minimum efficacious dose associated with less complication is 25 mcg [38], while the vaginal compared with the oral route appears to offer significant clinical advantage in successful vaginal delivery [39]. Dinoprostone is prostaglandin E2 that comes in two popular preparations as Cervidil, a control release hydrogel suppository 10 mg vaginal inserted every 12 h at 0.3 mg/h.…”
Section: Prostaglandinsmentioning
confidence: 99%
“…Following completion of the electronic search strategy we were able to identify 1436 potentially relevant articles. After reading the abstracts and, when needed, full texts we managed to limit them to an overall number of 69 articles of which we finally selected 57 randomized trials that involved 10,975 parturient [ 15 – 70 ]. The methodological characteristics of included studies as well as patient characteristics are depicted in the “ Appendix ” and reveal comparable groups of oral vs vaginal misoprostol intake in terms of maternal age and body mass index, gestational age at delivery parity, Bishop score prior to the start of induction and neonatal birthweight.…”
Section: Resultsmentioning
confidence: 99%
“…P.R.O.M 8. Antepartum haemorrhage NA 25 µg sublingually 25 µg vaginally 102 included Compare the efficacy of sublingual versus vaginal misoprostol for induction of labour in primigravida at term DebBarma (2020) [ 70 ] 1.Single live fetus 2.Cephalic presentation 3.Gestaional age > 37w 4.Bishop score < 5 5. Intact membrane 6.…”
Section: Appendixmentioning
confidence: 99%
“…Main problem reported with vaginal misoprostol is uterine hyper stimulation and excessive contractions which is common with high dose and specially when used in multigravida. 16 Earlier studies have reported that when misoprostol is administered correctly, the absolute hazards are modest. Vaginal misoprostol reduced the time from IOL to vaginal birth compared to other techniques of labor induction and augmentation, but it did not lower the rate of the cesarean section when compared to oral misoprostol.…”
Section: Discussionmentioning
confidence: 99%
“…Main problem reported with vaginal misoprostol is uterine hyper stimulation and excessive contractions which is common with high dose and specially when used in multigravida. 16 …”
Section: Discussionmentioning
confidence: 99%